The Association between Malaria and β-Carotene Levels: A Systematic Review and Meta-Analysis - Kwuntida Uthaisar Kotepui; Aongart Mahittikorn; Polrat Wilairatana; Frederick Ramirez Masangkay; Manas Kotepui (Antioxidants, 2023)
Background: β-Carotene, which is a prominent carotenoid with notable antioxidant properties, may play a role in countering the oxidative stresses induced by malaria. The association between β-carotene levels and malaria is not yet fully understood, prompting this systematic review and meta-analysis. Methods: A rigorous search of databases, including Nursing and Allied Health Premium, EMBASE, MEDLINE, Ovid, PubMed, Scopus, and Google Scholar, was undertaken to collate studies that focused on β-carotene levels in malaria patients. The selected studies underwent critical appraisal, followed by data extraction for a meta-analysis. Results: Of the 2498 records initially identified, 10 were deemed suitable for synthesis. A considerable number of these studies indicated a pronounced reduction in β-carotene levels among malaria patients in contrast with uninfected individuals. The meta-analysis, encompassing 421 malaria patients and 240 uninfected controls, revealed a significant correlation between reduced β-carotene levels and malaria (p < 0.01, Hedges’s g: −1.26, 95% CI: −2.00–(−0.53), I2: 93.86%, seven studies). Conclusions: The conducted systematic review and meta-analysis corroborated the correlation between lower β-carotene levels and malaria. The intricate relationship between malaria and β-carotene merits deeper exploration. A comprehensive understanding of this association might pave the way for innovative therapeutic approaches leveraging the antioxidant attributes of β-carotene to combat malaria-induced oxidative stress.